SSTC - Nábělek, F. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Document provide information regarding adjustment of power source, implementing those changes into whole equipment. Final solution and choosing best solution for whole assembly is supported by lab measuring. Main update of power source is based on 50% reduction of secondary coil winding. In section of completing whole assembly is highlighted affect to functionality and design. Measurement section presented facts about inductance of coil, affects to frequency of exciter signal and observation of power consuption based on frequency modulation.
Keywords: Alternation of power source; assembly; measurement